Efektivitas pendidikan agama Islam berbasis digital dalam pembentukan akhlak mulia siswa Madrasah Ibtidaiyah di Era society 5.0 studi kasus di Provinsi Jambi - Ratna Puspitasari (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2026)
The rapid development of digital technology in the era of Society 5.0 has significantly transformed educational practices, including Islamic education at the elementary level. However, the integration of digital technology in Islamic learning raises concerns regarding students’ moral and character development due to unrestricted access to information and digital media exposure. This study aims to analyze the implementation and effectiveness of digital-based Islamic education in shaping noble character among Madrasah Ibtidaiyah students in Jambi Province, Indonesia. The research employed a qualitative case study approach involving Islamic education teachers, principals, students, and parents from several Madrasah Ibtidaiyah institutions in Jambi Province. Data were collected through interviews, classroom observations, documentation, and questionnaires. The findings reveal that digital-based Islamic education positively contributes to the development of students’ discipline, honesty, responsibility, religiosity, and social ethics when supported by appropriate supervision, Islamic values integration, and interactive digital learning media. The study also identifies several challenges, including limited digital literacy among teachers, inadequate infrastructure, and weak parental control over students’ digital activities. Nevertheless, digital learning provides opportunities for personalized learning, interactive religious instruction, and broader access to Islamic educational resources. This study contributes to the discourse on digital Islamic education and highlights the importance of integrating technology with moral education in the Society 5.0 era.